Safety of Upper Pole Puncture in Percutaneous Nephrolithotomy with the Guidance of Ultrasonography versus Fluoroscopy: A Comparative Study - TANIDIR, YILÖREN (KARGER, 2020)
Introduction:The aim of this study was to compare the safety of ultrasonography-guided (UG) puncture and fluoroscopy-guided (FG) upper pole access (UPA) in percutaneous nephrolithotomy (PCNL).Methods:Consecutive patients with a solitary UPA were enrolled into the study from 2012 to 2020 and analyzed in a retrospective manner. In total, 177 patients were divided into 2 groups according to the method during the puncture phase of the access: FG (n= 105) and UG (n= 72). The UG and FG groups were compared in terms of complications (i.e., pleural injury and blood transfusion rate) and surgical outcomes.Results:Gender, side, grade of hydronephrosis, type of access (i.e., supracostal vs. subcostal), Guy's stone score, age, stone diameter, skin-to-stone distance, and stone density were similar in the 2 groups (p> 0.05). Only in 25.9% of cases, UPA was done using a subcostal approach. The overall complication rates were similar between the groups (p> 0.178). For the UG and FG groups, the rate of pleural injury (8.5 vs. 4.1%) and the blood transfusion rate (8.5 vs. 2.8%) were also similar (p> 0.05). The fluoroscopy time and mean hemoglobin drop were significantly lower in the UG group than in the FG group (134.2 vs. 82.2 s, respectively,p= 0.001; 20.8 +/- 9.8 vs. 16.8 +/- 7.9 g/L, respectively,p= 0.001). Stone-free rate (SFR) was also similar in the FG and UG groups (77.1 vs. 75.0%, respectively,p= 0.742).Conclusion:While it is commonly expected that the complication rates are lower in UG puncture for UPA in PCNL than they are in FG puncture, the present study failed to show this difference. However, the radiation exposure time seemed to be lower in UG puncture than FG puncture and had a similar stone-free rate (SFR) for UPA in PCNL.
Keywords: Upper pole puncture; Ultrasonography-guided puncture; Fluoroscopy-guided puncture; Safety; Percutaneous nephrolithotomy; SUPRACOSTAL APPROACH; RENAL ACCESS; ULTRASOUND; COMPLICATIONS; EFFICACY; OUTCOMES; PCNL